Шляхи подолання бар'єру при переході асинхронних двигунів до класу енергоефективності IE5 - Дзеніс, Сергій Євгенович; Шайда, Віктор Петрович; Юр'єва, Олена Юріївна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Застосування енергоефективних електродвигунів у промисловості дозволяє більш раціонально використовувати енергетичні ресурси і скоротити викиди парникових газів. Зважаючи на те, що у промисловості переважно використовуються асинхронні двигуни із фіксованою частотою обертання, завдання підвищення їхньої енергоефективності є актуальним. Встановлено, що головним обмежувальним фактором підвищення енергоефективності асинхронних двигунів до рівня IE5, є його тепловий стан. Аналіз шляхів підвищення ефективності асинх-ронних двигунів вказує на необхідність їх комплексного застосування. Найбільш доцільним є проведення оптимізації та удосконалення елементів системи повітряного охолодження асинхронних двигунів. Для проведення дослідження потрібно комплексно застосовувати системи моделювання електромагнітного та температурного поля асинхронних двигунів. Враховуючи певні недоліки теплових моделей асинронних двигунів необхідно поєднувати моделювання із експериментальними дослідженнями як за допомогою класичних датчиків температури, так і методу термографії.

Purpose. To provide a comprehensive analytical review on ways to increase the energy efficiency of induction motors and identify those suitable for transitioning fixed speed induction motors to IE5 level. Methodology. A thorough study of research and development in the field of increasing the energy efficiency of induction motors for various purposes was conducted. The experience of the development of traction induction motors of electric vehicles as dynamically developing is extrapolated. Results. It was established that the main limiting factor in increasing the energy efficiency of induction motors to the IE5 level is its thermal state. Analysis of ways to improve the efficiency of induction motors indicates the need for their com-plex application. It is most expedient to optimize and improve the elements of the air-cooling system of induction motors. To carry out the research, it is necessary to comprehensively apply electromagnetic and temperature field modeling systems of induction motors. Given certain shortcomings of thermal models of induction motors, it is necessary to combine modeling with experimental studies using both classical temperature sensors and the method of thermography. Originality. The combination of modern methods of modeling the thermal state of induction motors and experimental studies makes it possible to determine reserves for increasing the efficiency of existing motors. Using these results, it is possible to improve induction motors to the IE5 efficiency level. Practical value. Manufacturers and researchers see difficulties with the transition of induction motors of industrial purpose to the IE5 efficiency level, so they focused their attention on synchronous electric motors. The results of our research prove that, despite certain barriers, this transition can be made, albeit with certain difficulties.
Ways to overcome the barrier during the transition of asynchronous motors to the energy efficiency class IE5
Keywords: енергоефективний двигун; асинхронні двигуни; тепловий стан; система повітряного охолодження; energy-efficient motor; squirrel-cage induction motor; thermal state; air cooling